Chế tạo chất hấp phụ từ bã chè và ứng dụng cho hấp phụ thuốc diệt cỏ 2,4-dicolorophenenoxyaxetic axit trong môi trường nước - Thành, Nguyễn Văn; Hương, Đỗ Trà; Nghĩa, Hà Ngọc; Minh, Nguyễn Ngọc (Vietnam Journal of Chemistry, 2016)
Adsorbent was prepared from tea residue by H2SO4 activation (TRA), and was applied to remove 2,4-dichlorophenoxyacetic acid (2,4-D) from aqueous solution. The TRA was characterized by scanning electron microscopy (SEM) technique. The influence of pH (1.5-11), contact time (30-240 min), and the amount of adsorbent (0.01-0.05 g) on 2,4-D removal efficiency by the TRA were also investigated. The results show that the time to reach adsorption equilibrium, the optimal pH value for adsorption of 2,4-D and the the amount of adsorbent of TRA are 150 min, 2.5 and 0.05 g, respectively. The maximum monolayer adsorption capacity of TAC is 156.25 mg/g. The as-prepared TAC therefore acts as a promising adsorbent for the pesticide removal from the polluted water. Keywords. Adsorption, tea residue, Langmuir isotherm, pesticides, 2,4-D.